Evolutionary relationships of Bresadolia (Basidiomycota, Polyporales) based on molecular and morphological evidence - Motato-Vásquez, Viviana (2018)
In the last decades, several phylogenetic studies have shown that Polyporus is polyphyletic; accordingly, several genera have been newly described or reinstated. Nevertheless, the phylogenetic position of many species in the genus remains highly contentious, particularly those traditionally included in the Polyporus infrageneric group Polyporuss.s.,i.e.,P. austroafricanus, P. craterellus,P. radicatus, P. squamosus, P. tuberaster, and P. udus. Recently, based on morphological characteristics, P. udus, described from Indonesia, was synonymized with Bresadolia paradoxa, described from Paraguay, resurrecting Bresadoliaas a good genus. In this study, the phylogenetic relationship of P. udus and its purported taxonomic synonym in South America was investigated. In addition, the phylogenetic positioning of Bresadolia within Polyporus s.l. and related genera was assessed, based on ITS and nLSU rDNA loci. Morphological revision of collections from the Atlantic Forest of Argentina, Brazil, and Paraguay; revision of type specimens; and the phylogenetic results showed that B. paradoxa and P. udus are not conspecific. Both species form independent lineages that cluster together within a monophyletic genus recognized here as Bresadolia. In thisstudy, a complete description of B. paradoxa incorporating data of type specimens previously overlooked and characters from se-quenced fresh specimens is provided, as well as comments on all species described or combined in Bresadolia